Karakterisitik Meso-Size Marine Debris di Kawasan Wisata Pesisir Barat Kota Mataram: Characteristics of Meso-Sized Marine Debris in Tourist Destinations on the West Coast of Mataram City - Ayu Adhita Damayanti; Chandrika Eka Larasati; Sadikin Amir; Bagus Dwi Hari Setyono; Dewi Putri Lestari (LPPM Universitas Mataram, 2022)
Marine debris severely threatens the balance of marine ecosystems. Toxic waste content can contaminate water and substrates. The physical form of hard and sharp waste material can hurt marine organisms. This research aims to analyze the characteristics of meso sized marine debris in tourist destinations on west coast of Mataram city. Samples were collected at two stations that representing the tourist destinations on west coast of Mataram City, namely Penghulu Agung Beach and Ampenan Beach. Waste measurement using a 3 transect system measuring 10x10 m which is divided into 10 plots measuring 1x1 m for each station. Waste observed in this research was meso-size marine debris. Each item were identified, then calculated for relative density and density per item based on number and weight. Based on the results of the research, 10 categories of waste were obtained at both stations. This type of waste includes plastic, rubber paper, textiles, wood, metal, glass, ceramics, hazardous and toxic materials (B3), and other waste. Plastic waste dominates at both stations, reaching 68% for Station I and 75% for Station II. The density of waste is higher at Station II with an average of 8.67 items.m-2 compared to Station I with an average of 3.33 items.m-2. At Station I there is an average of 2.27 items.m-2 of plastic waste while in station II, plastic waste is much higher, which is 6.47 items.m-2. The average weight of total meso-sized waste collected from stations I and II is 2.78 g.m-2. Station I has a total waste weight of 0.56 g.m-2 and station II weight 4.99 g.m-2. The highest waste weight is for plastic waste type which is 0.24 g.m-2 at station I and 2.49 g.m-2 at station II.